2020
DOI: 10.1021/acs.jafc.0c01466
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Chemical Fate of [36Cl]Chlorine Dioxide Gas on Avocados, Eggs, Onions, and Sweet Potatoes

Abstract: Fate and distribution studies were conducted with [ 36 Cl]-chlorine dioxide in avocados, eggs, onions, and sweet potatoes. Experiments utilized sealed, darkened chambers, 5 mg of 36 ClO 2 (g), and two-hour exposure periods. Total radioactive residues were quantitated in gas purges, tank rinses, reaction chambers, and on fractions specific to each food. Deposition of the radioactive residue was mostly a surface phenomenon; transfer of radioactivity into albumen occurred in egg, but radioactivity did not penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It can be generated with dry precursors eliminating the need for hazardous chemical storage. It breaks down into chlorate and chlorite ions as byproducts of sodium chlorite and leaves behind little to no residues post-treatment (G omez-L opez, Rajkovic, Ragaert, Smigic, & Devlieghere, 2009;Smith & Scapanski, 2020;Trinetta, Vaidya, Linton, & Morgan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It can be generated with dry precursors eliminating the need for hazardous chemical storage. It breaks down into chlorate and chlorite ions as byproducts of sodium chlorite and leaves behind little to no residues post-treatment (G omez-L opez, Rajkovic, Ragaert, Smigic, & Devlieghere, 2009;Smith & Scapanski, 2020;Trinetta, Vaidya, Linton, & Morgan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of knowledge with regards to the optimum initial dose to prevent any damage to the fruits. In addition, recent studies have concluded that a slow controlled release of ClO 2 using dry precursors resulted in undetectable amounts of chlorate and chlorite residues ( Smith and Scapanski, 2020 ). The lack of chemical residue is very important in order to maintain industry standards.…”
Section: Discussionmentioning
confidence: 99%
“…But under dark conditions, treatment of ready‐to‐eat salami with gaseous ClO 2 did not cause the formation of any measurable residues (limit of detection: 4 ng/g) of sodium perchlorate (Smith et al., 2016). Moreover, studies of such residues via radio‐labeling showed some residues in treated fresh eggs, but not in the consumed portion of raw onions, and only to a small degree in avocado flesh (Smith & Scapanski, 2020). Another study found that any residual gaseous ClO 2 after fumigation declines to <1 mg/L after 14 days, indicating a natural dissipation of gaseous ClO 2 over time (Wu & Rioux, 2010).…”
Section: Effects Of Gaseous Chlorine Dioxide Treatment On Food Qualitymentioning
confidence: 99%